Transatlantic relations after the Covid-19 pandemic. Issue 2 (October 2020) - Arvanitopoulos, Constantine
This article analyses how the COVID-19 pandemic has affected the relationship between Europe and the US, and provides suggestions on how transatlantic cooperation should be taken forward. The pandemic has increased public distrust of the US in Europe due to the way the former has chosen to respond to COVID-19. However, this article argues that the pandemic has mainly accelerated existing transatlantic differences rather than creating new ones. To restore the transatlantic relationship, Europe and the US should strengthen their cooperation on common challenges such as climate change, health security, China, terrorism and migration. COVID-19 has highlighted the limitations of nationalist and unilateral policies in confronting global challenges. It may, in the end, provide the impetus for a rejuvenated transatlantic partnership and build a renewed sense of transatlantic solidarity.